2006
DOI: 10.1111/j.1529-8027.2006.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal sural nerve conduction study in vitamin B12 deficiency with megaloblastic anemia

Abstract: Peripheral neuropathy is frequently observed in B(12) deficiency. In spite of this, there is little knowledge about peripheral neuropathy in B(12) deficiency because the severity of clinical involvement of the central nervous system clearly outweighs signs and symptoms due to peripheral nervous system involvement. We primarily investigated peripheral neuropathy with dorsal sural conduction study, which is a new method for detection of early peripheral neuropathy, in B(12) deficiency with megaloblastic anemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…[2610111213] Similarly, in the present study, dorsal sural response could be obtained in all the participants, the oldest participant being 90 years old. In two participants who had a callus below and behind the lateral malleolus, the SNAP was difficult to obtain, and the study was abandoned.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…[2610111213] Similarly, in the present study, dorsal sural response could be obtained in all the participants, the oldest participant being 90 years old. In two participants who had a callus below and behind the lateral malleolus, the SNAP was difficult to obtain, and the study was abandoned.…”
Section: Discussionsupporting
confidence: 81%
“…In a study of dorsal sural conduction in megaloblastic anemia, absent responses were found in 54% patients whereas remaining patients had mean lower amplitude, longer latency, and slower conduction velocity as compared to healthy control participants. [13] This signified the importance of cutoff values of dorsal sural conduction to identify early peripheral neuropathy rather than relying on the mere presence or absence of dorsal sural SNAP. The present study on dorsal sural conduction defined important cutoff values for lower limit of normal for amplitude and velocity in three age groups in western Indian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed improvements in sensory nerve conduction in the lower extremities. The sensory fibers are usually the first to be affected by vitamin B-12 deficiency (15,16) and an evaluation of sural nerve function has been suggested as an early indicator of peripheral nerve deterioration (29). The neurophysiologic evaluation of our participants also included QST and SSEPs, but no changes were observed in these variables after the vitamin B-12 injection, possibly because an improvement in vitamin B-12 status affects mainly large afferent peripheral nerves rather than the smaller fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory polyneuropathy is also observed in vitamin B-12 deficiency (8) and involves myelinated large-caliber afferent fibers (7,8). Although the clinical and neurophysiologic features of symptomatic vitamin B-12 deficiency in patients with neurologic manifestations have been reported (6,9), most reports have been from case studies of elderly subjects with pernicious anemia who received a variety of treatments and different followup assessments (10)(11)(12)(13) or have only studied small groups of participants (7,(14)(15)(16). It is not well established whether impairments in neurologic function occur in population groups with poor vitamin B-12 status but no clinical symptoms of deficiency (17) or whether changes in function can be achieved through vitamin B-12 supplementation.…”
Section: Introductionmentioning
confidence: 99%